Value of EEG in Antiepileptic Drug Withdrawal - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The prognostic value of the EEG in 120 seizure-free epileptic patients, during and after antiepileptic drug withdrawal, was analyzed at the Department of Neurology, University of Bologna, Italy.